The Disclosure of Sustainability Report in Energy and Financial Sector Companies of Indonesia and Malaysia Sharia Securities List - Aneta Rakhmawati; Oktria Fani Rahmasari (P3M Politeknik Negeri Banjarmasin, 2024)
This study aims to determine the level of sustainability report disclosure in energy and financial sector companies of Indonesia and Malaysia sharia securities list in 2021. Sustainability report is an important measurement tool for the government and stakeholders to see the extent of a company's sustainability performance. This study focuses on analyzing the level of sustainability report disclosure on economic, environmental, and social topics based on the GRI Standards by using qualitative-descriptive research type. The number of samples in this study is 21 companies which was taken based on purposive sampling. The results of this study indicate that the average of sustainability report disclosure for 2021 in the energy sector is higher than the disclosure score made by financial sector. The average disclosure of the energy sector is 41,45%, while the financial sector is 27,53%. Indonesia obtained the highest score for energy sector while Malaysia obtained the highest score for financial sector. The highest disclosure rate for financial sector is owned by Bursa Malaysia Bhd with a score 35,96%. Meanwhile, the highest disclosure rate for the energy sector is occupied by PT Perusahaan Gas Negara Tbk with a total score 77,53%.